Áp dụng thuật toán tách tiền chấn và dư chấn từ danh mục động đất Đông Nam Á - Lư, Ngô Thị (Vietnam Journal of Earth Sciences, 2000)
Application of the algorithm for allocation offoreshocks and aftershocks in an earthquakecatalogue of Southeast Asia